Mechanisms and therapeutic prospects of hypoxia-inducible factor 1-alpha in acute kidney injury: a systematic review - Kang, Peng; Cheng, Fan (Frontiers in Cell and Developmental Biology, 2026)
BackgroundAcute Kidney Injury (AKI) poses a significant global health challenge, with increasing incidence and mortality rates, and profoundly impacts long-term outcomes, including progression to chronic kidney disease. Ischemia-reperfusion injury (IRI) is a major cause of AKI, in which hypoxia-inducible factor-1α (HIF-1α) plays a complex and dual role.MethodsThis review systematically analyzes the regulatory functions of HIF-1α in renal IRI, focusing on molecular mechanisms involving oxidative stress, apoptosis, inflammation, and tissue repair.ResultsEmerging evidence from preclinical studies demonstrates that HIF-1α orchestrates key adaptive responses in renal IRI, including the regulation of mitophagy, management of endoplasmic reticulum stress, and induction of metabolic reprogramming toward glycolysis.ConclusionTargeting HIF-1α represents a promising therapeutic strategy for AKI. Advances in HIF-1α-modulating therapies, particularly HIF prolyl hydroxylase inhibitors, offer novel avenues for both prevention and treatment. These findings underscore the potential for HIF-1α-centered therapies to mitigate AKI progression and improve clinical outcomes.